Analisis Usahatani Jambu Air (Syzygium Samarangense) Desa Mranak Kecamatan Wonosalam Kabupaten Demak - lutfiani, Dwi; Wahyuningsih, Sri; Istanto, Istanto (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
Analysis of the pomegranate guava farming business in Mranak Village provides an overview of the economic contribution of this sector to the region. This research aims to analyze the costs, revenues, income, BEP and R/C of the water guava business in Dempet Mranak Village, Wonosalam, Demak Regency. The method used in this research used a descriptive method. This research was carried out in the last post-harvest month of October-November 2023. The number of farmers involved in this research was 12 water apple farmers. The research results show that the average total costs incurred are Rp. 4,497,917/harvest/0.7 Ha on own land, the average production amount is 1,383 Kg/harvest season/0.7 Ha and the average selling price is IDR 10,000/Kg, resulting in an average total revenue of IDR 13,833,333/harvest season/0.7 Ha, resulting in an average income of IDR 9,335,417/0.7Ha/harvest season. The average production BEP calculation is 449.8/Kg/0.7Ha/harvest season and the price BEP is IDR 3,626/0.7Ha/harvest season. The price BEP and unit BEP are both smaller than the market price and production quantity. The average RC ratio for water guava farming is 3.07